2001
DOI: 10.1108/00483480110380325
|View full text |Cite
|
Sign up to set email alerts
|

Islamic work ethic – A moderator between organizational commitment and job satisfaction in a cross‐cultural context

Abstract: This study investigates the moderating impacts of the Islamic work ethic on the relationships between organizational commitment and job satisfaction. It uses a sample of 425 Muslim employees in several organizations in the United Arab Emirates (UAE). The empirical results indicate that the Islamic work ethic directly affects both organizational commitment and job satisfaction, and that it moderates the relationship between these two constructs. Results further reveal that national culture does not moderate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
417
3
33

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 365 publications
(485 citation statements)
references
References 66 publications
32
417
3
33
Order By: Relevance
“…Parenall (2003) found the partial relationship between these two variables while William and Hacks (1986) found a strong positive relationship between job satisfaction and organizational commitment. Other studies (Yousef, 2001;Chen, 2007;Allen et al, 2003) have also investigated the relationship between job satisfaction and employee's organizational commitment but mixed results were found. Job satisfaction positively effects affective and normative commitment but not continuance commitment (Meyer & Allen, 1997;Celik, n.d.).…”
Section: Relationship Between Job Satisfaction and Organizational Commentioning
confidence: 92%
“…Parenall (2003) found the partial relationship between these two variables while William and Hacks (1986) found a strong positive relationship between job satisfaction and organizational commitment. Other studies (Yousef, 2001;Chen, 2007;Allen et al, 2003) have also investigated the relationship between job satisfaction and employee's organizational commitment but mixed results were found. Job satisfaction positively effects affective and normative commitment but not continuance commitment (Meyer & Allen, 1997;Celik, n.d.).…”
Section: Relationship Between Job Satisfaction and Organizational Commentioning
confidence: 92%
“…The few scholars who have conducted studies on IWE and related concepts include Ali (1988Ali ( , 1992, Yousef (2000Yousef ( , 2001, Rahman et al, (2006), Ali and Al-Kazemi, (2007), and Khali andAbu-Saad (2009). Yousef (2001) investigated the moderating effect of the IWE on the relationship between organisational commitment and job satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Blood (1969) found that religious ethics (Protestant) have positive correlation with job satisfaction. This is supported by Yousef (2001) that religious values through work ethic have a positive relationship with work satisfaction. Therefore both research supports that religious values have a positive impact on work satisfaction and coincidentally, belief in God is also the number one value in the MAF.…”
Section: Job Satisfactionmentioning
confidence: 49%